2018
DOI: 10.1152/advan.00188.2017
|View full text |Cite
|
Sign up to set email alerts
|

Peer teaching beyond the formal medical curriculum

Abstract: Peer-assisted learning (PAL) is nowadays commonly implemented in medical education. Mostly PAL is utilized to specifically support teaching within one subject or a specific curricular situation. Here, we present a large-scale peer teaching program that aims to address the individual student's learning needs. In addition, it provides a platform for students to participate in academic teaching. A retrospective data analysis was performed to reveal the program's development and acceptance. The program was impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 47 publications
2
19
0
4
Order By: Relevance
“…Findings from the questionnaire demonstrated that most students had a positive perception toward peer learning, which is in line with most research findings [ 2 , 26 ]. However, it seems that the benefits of peer learning were limited as most students were reluctant to recommend implementing peer learning in other courses.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Findings from the questionnaire demonstrated that most students had a positive perception toward peer learning, which is in line with most research findings [ 2 , 26 ]. However, it seems that the benefits of peer learning were limited as most students were reluctant to recommend implementing peer learning in other courses.…”
Section: Discussionsupporting
confidence: 88%
“…Peer learning is defined as “people from similar social groupings, who are not professional teachers, helping each other learn, and by so doing, learning themselves” [ 1 ]. Peer learning can be categorized into (1) same-level peer learning where students at equal academic levels discus and study the materials together and (2) cross-level peer learning where students’ academic levels diverge [ 2 ]. Peer learning is rapidly gaining acceptance and there are supporting evidences for peer learning in clinical skill development worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Although PAL implementation is becoming more widely adopted in UGME, faculty remain the cornerstone of medical education instruction. PAL in medical physiology teaching has commonly been implemented as supplemental instruction to complement faculty-led instruction (4,6). This study suggests that smallgroup-based PAL could effectively supplement faculty-led review sessions, even in a discipline as complex as medical physiology.…”
Section: Resultsmentioning
confidence: 93%
“…In anatomy courses, students perceived PAL as an effective method for learning anatomy using cadaveric specimens (1), and student experiences with peers were rated favorably (14). In physiology courses, implementation of a large-scale PAL program has been demonstrated to benefit both tutors and tutees to complement the formal curriculum (4). Successful PAL execution results in well-described, short-term improvements in students' perceived understanding of physiological principles and satisfaction with preclerkship instruction (3,6), demonstrating benefits for student tutors, tutees, and medical education programs (16).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of PAL activities are increasingly used in medical education, commonly in combination with other methods, for both basic science and clinical courses. These activities can be broadly grouped into peer tutoring, peer teaching, and peer mentoring (Burgess et al, 2014; Engels et al, 2018).…”
Section: Introductionmentioning
confidence: 99%